Membangun Moderasi Beragama di Kalangan Santri Melalui Peran Pengelolaan Lembaga Pendidikan Dayah di Aceh - Razali Mahmud; Yustizar Yustizar; Yusaini Yusaini; Adelina Nasution (Turast: Jurnal Penelitian dan Pengabdian, 2023)
This article aims to describe the role of Ulama as Dayah managers in building an attitude of moderation and providing an ideal concept of religious moderation among students at Dayah Education institutions in Aceh. The service is carried out by mentoring which is carried out jointly with the Dayah manager. In mentoring the servant observes the application and understanding of the concept of moderation that occurs among the santri, and ends by providing material and the concept of religious moderation to the santri through presentation of the material and through group communication in the activities of the santri at the Dayah Education Institute. Prior to the introduction of the concept of religious moderation at Daya, it was found that the students had errors in understanding or interpreting the teachings of the sciences given and this had a serious impact on their practice in social and state life, such as giving birth to students who were anti-tolerant, radical so that they fell into religious organizations. terrorism organization. The results of the dedication obtained a belief that Dayah in Aceh as an Islamic education has a great responsibility in equipping his students to be moderate. Thus teachers, administrators to the head of the Islamic boarding school are expected to first have the character of religious moderation. Not a few students who are at the Aceh Dayah educational institution have been contaminated with radical mindsets because there are still many teachers or religious teachers who guide these students to instill anti-tolerant concepts due to certain interests. So that the role of Islamic education institutions is appropriate in collaborating on curriculum or SOPs for students to form the character of religious moderation. This service uses the Participation Action Research (PAR) method, namely acting as a facilitator or companion. So that the Management of the Dayah educational institution can echo and invite its students and alumni to have a moderate Muslim mindset. Artikel ini bertujuan untuk mendeskripsikan peran ulama sebagai pengelola Dayah dalam membangun sikap moderasi dan memberikan konsep moderasi beragama secara ideal di kalangan santri pada lembaga Pendidikan Dayah di Aceh. Pengabdian dilakukan dengan cara pendampingan yang dilakukan secara bersama dengan pengeloala Dayah. Dalam pendampingan pengabdi mengobservasi penerapan dan pemahaman konsep moderasi yang terjadi di kalangan santri, dan akhiri dengan pemberian materi dan konsep moderasi beragama kepada para santri melalaui pemaparan materi dan melalui komunikasi kelompok dalam aktivitas santri di Lembaga Pendidikan dayah. Sebelum pemberian konsep moderasi beragama dilaksanakan di Daya, para santri ditemukan adanya kesalahan dalam memahami atau memaknai ajaran ilmu yang diberikan dan hal ini berdampak serius pada pengamalanya dalam kehidupan bermasyarakat dan bernegara, seperti melahirkan santri-santri yang anti toleran, Radikal hingga terjerumus kedalam organisasi-organisasi terorisme. Hasil pengabdian diperoleh satu keyakinan bahwa Dayah di Aceh sebagai pendidikan islam memiliki tanggung jawab besar dalam membekali satri-santrinya agar bersikap moderat. Dengan demikian pengajar, pengelola hingga kepala dayah diharapkan terlebih dahulu memiliki karakter moderasi beragama. Tidak sedikit santri-santri yang berada di Lembaga pendidikan Dayah Aceh sudah terkontaminasi dengan pola pikir radikal dikarenakan masih banyak pengajar atau ustad-ustad yang membimbing santri-santri tersebut menanamkan konsep-konsep anti toleran dikarenakan kepentingan tertentu. Sehingga dengan demikian sudah sepantasnya peran Lembaga pendidikan dayah mengkolaborasikan kurikulum atau SOP pembelajarnya pembentukan karakter moderasi beragama. Pengabdian ini Menggunakan metode dalam Partisipation Action Reasearch (PAR) yaitu berperan sebagai fasilitator atau pendamping. Sehingga Pengelolaan Lembaga pendidikan Dayah ini dapat menggaungkan dan mengajak santri-santri dan alumninya memiliki pola pikir muslim yang moderat.